Raman Pumping as an Energy Efficient Solution for NyWDM Flexible-grid Elastic Optical Networks - Arsalan Ahmad; Andrea Bianco; Vittorio Curri; Guido Marchetto; Sarosh Tahir (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper investigates transparent wavelength routed optical networks using three different fiber types NZDSF, SMF and PSCF - and validates the effectiveness of Hybrid Raman/EDFA Fiber Amplification (HFA) with different pumping levels, up to the moderate 60% pumping regime. Nodes operate on the basis of flexible-grid elastic NyWDM transponders able to adapt the modulation format to the quality-of-transmission of the available lightpath, exploiting up to five 12.5 GHz spectral slots. Results consider a 37- node Pan-European network for variable Raman pumping level, span length and average traffic per node. We show that HFA in moderate pumping regime reduces the power consumption and enhances spectral efficiency for all three fiber types with particular evidence in NZDSF. In essence to that, introduction of HFA is also beneficial to avoid blocking for higher traffic loads.